Cognitive Impairment Involving Social Cognition in SPG4 Hereditary Spastic Paraplegia - Ludivine Chamard; Sabrina Ferreira; Alexa Pijoff; Manon Silvestre; Eric Berger; Eloi Magnin (Behavioural Neurology)
Objectives. To describe cognitive assessment including social cognition in SPG4 patients. Methods. We reported a series of nine patients with SPG4 mutation with an extensive neuropsychological examination including social cognition assessment. Results. None of our patients presented with mental retardation or dementia. All presented with mild cognitive impairment with a high frequency of attention deficit (100%), executive disorders (89%), and social cognition impairment (78%). An asymptomatic patient for motor skills presented with the same cognitive profile. No correlation was found in this small sample between cognitive impairment and motor impairment, age at disease onset, or disease duration. Conclusions. SPG4 phenotypes share some cognitive features of frontotemporal lobar degeneration and amyotrophic lateral sclerosis. Cognitive disorders including executive disorders and social cognition impairment are frequent in SPG4 patients and might sometimes occur before motor disorders. Therefore, cognitive functions including social cognition should be systematically assessed in order to improve the clinical management of this population.